Selection of Additional Materials for the Production of Paving Blocks - Fachriza Noor Abdi; Dutho Suh Utomo (IJESS International Journal of Education and Social Science, 2023)
Additional materials in the manufacture of paving blocks are needed as additional materials to produce paving that meets the required criteria. There are several criteria that can be considered in selecting the criteria for these additives, including compressive strength, splitting tensile strength and permeability. The existence of multi-criteria requires a multi-criteria selection method so that those selected are in accordance with the criteria, therefore the TOPSIS method is used. In this case the decision maker prioritizes permeability as the first criterion, followed by compressive strength and splitting tensile strength with the same interests. The results in this study that the highest weight value was rice husk ash with a value of 0.657 compared to the other two additional ingredients, namely fly ash and palm shell ash. Therefore, rice husk ash is the best choice based on decision making criteria.